Regulation of PV interneuron plasticity by neuropeptide-encoding genes - Martijn Selten; Clémence Bernard; Diptendu Mukherjee; Fursham Hamid; Alicia Hanusz-Godoy; Fazal Oozeer; Christoph Zimmer; Oscar Marín (Nature, 2025)
Abstract Neuronal activity must be regulated in a narrow permissive band for the proper operation of neural networks. Changes in synaptic connectivity and network activity—for example, during learning—might disturb this balance, eliciting compensatory mechanisms to maintain network function 1–3 . In the neocortex, excitatory pyramidal cells and inhibitory interneurons exhibit robust forms of stabilizing plasticity. However, although neuronal plasticity has been thoroughly studied in pyramidal cells 4–8 , little is known about how interneurons adapt to persistent changes in their activity. Here we describe a critical cellular process through which cortical parvalbumin-expressing (PV + ) interneurons adapt to changes in their activity levels. We found that changes in the activity of individual PV + interneurons drive bidirectional compensatory adjustments of the number and strength of inhibitory synapses received by these cells, specifically from other PV + interneurons. High-throughput profiling of ribosome-associated mRNA revealed that increasing the activity of a PV + interneuron leads to upregulation of two genes encoding multiple secreted neuropeptides: Vgf and Scg2 . Functional experiments demonstrated that VGF is critically required for the activity-dependent scaling of inhibitory PV + synapses onto PV + interneurons. Our findings reveal an instructive role for neuropeptide-encoding genes in regulating synaptic connections among PV + interneurons in the adult mouse neocortex.